2016
DOI: 10.1177/0022034516656838
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots as Nonagglomerated Nanofillers for Adhesive Resins

Abstract: Nanoparticles used in adhesive resins are prone to agglomeration, turning the material susceptible to physical failure. Quantum dots are nonagglomerated inorganic nanoparticles (1 to 10 nm) when in equilibrium. The aim of the present study was to synthesize and characterize zinc oxide quantum dots (ZnO) and to develop and evaluate an adhesive resin with the addition of ZnO. ZnO were formulated by self-organization in chemical reaction with isopropanol and added to 2-hydroxyethyl methacrylate (HEMA). HEMA conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Besides that, from 2.5% wt on, the resistance to solvent degradation was improved. This is an advantage among antibacterial adhesives, as it was observed that other adhesives with antibacterial fillers could not present this result (18). In this study, although the materials presented no statistical difference in degree of conversion, the polymer chains may have been organized differently.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Besides that, from 2.5% wt on, the resistance to solvent degradation was improved. This is an advantage among antibacterial adhesives, as it was observed that other adhesives with antibacterial fillers could not present this result (18). In this study, although the materials presented no statistical difference in degree of conversion, the polymer chains may have been organized differently.…”
Section: Discussionmentioning
confidence: 63%
“…Specimens were then subjected to softening in absolute ethanol for 2 h at 37 °C and the microhardness values were measured again (KHN2). The percent difference was calculated according to a previous study (18).…”
Section: Softening In Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…It decreases the composite's organic phase and the adhesives may be more hydrolytic stable, as the water sorption occurs mainly in the organic matrix 29) . The adhesive resin must promote the distinction of the demineralized tissue (dentin or 4…”
Section: Discussionmentioning
confidence: 99%
“…Tests were performed in a test machine Shimadzu (EZ-SX; Shimadzu) at a crosshead speed of 1-mm/min. UTSs were calculated according to previous study 29) .…”
Section: Utsmentioning
confidence: 99%